MENINGKATKAN KEMAMPUAN MEMBACA MANDIRI KATA DAN KALIMAT DENGAN LAFAL YANG TEPAT MELALUI STRATEGI PROBLEM BASED LEARNING SISWA KELAS I SDN 2 MARGOSARI - RINI UDIASTUTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The purpose of this study was to improve the ability to read words and sentences independently with the correct pronunciation through a problem-based learning strategy for first grade students at SDN 2 Margosari. This research is a classroom action research. This classroom action research was conducted at SDN 2 Margosari, in class I with a total of 19 students for the 2022/2023 school year. The method used is a problem based learning strategy. Based on the results of the formative test score data after the improvement in cycle 1, it can be said that there is an increase in learning outcomes. This is indicated by the increase in the results of the formative test, which was originally only 6 students (30%) completed to 15 students (75%). The results of the formative test score data after improvement (cycle II) can be said that there is an increase in learning outcomes. This is indicated by the increase in formative test results, which originally only 15 students (75%) completed to 20 students (100%). Based on observations in Cycle II, students were active in participating in learning and in carrying out the teacher's duties well. It turns out that using problem based learning strategies to improve student learning outcomes is in accordance with the expected plans. ABSTRAKTujuan Penelitian ini untuk meningkatkan kemampuan membaca mandiri kata dan kalimat dengan lafal yang tepat melalui strategi problem based learning siswa kelas I SDN 2 Margosari. Penelitian ini merupakan penelitian tindakan kelas. Penelitian tindakan kelas ini dilakukan di SDN 2 Margosari, pada kelas I dengan jumlah siswa 19 siswa tahun ajaran 2022/2023. Metode yang di gunakan dengan strategi problem based learning. Berdasarkan hasil data nilai tes formatif setelah diadakan perbaikan siklus 1 dapat dikatakan bahwa ada peningkatan dalam hasil pembelajaran. Hal ini ditunjukkan dengan meningkatnya hasil tes formatif, yang semula ketuntasannya hanya 6 siswa (30%) menjadi 15 siswa (75%). Hasil data nilai tes formatif setelah diadakan perbaikan (siklus II) dapat dikatakan bahwa ada peningkatan dalam hasil pembelajaran. Hal ini ditunjukkan dengan meningkatnya hasil tes formatif, yang semula ketuntasannya hanya 15 siswa (75%) menjadi 20 siswa (100%).Berdasarkan pengamatan yang dalam Siklus II adalah siswa aktif dalam mengikuti pembelajaran serta dalam melaksanakan tugas guru dengan baik. Ternyata melalui menggunakan strategi problem based learning dalam meningkatkan hasil belajar siswa telah sesuai dengan rencana yang telah diharapkan.